The uncertain benefits of environmental reform in open economies - Larry S. Karp; Jinhua Zhao; Sandeep Sacheti (Fondazione Eni Enrico Mattei (FEEM), 1997)
We compare the instantaneous and the long run effects of environmental reform in closed and open economies. Harmonization upward (decreasing distortions where they are most severe) or harmonization downward (increasing distortions where they are less severe), both tend to increase instantaneous world welfare. Environmental reform in a country with less severe distortions works against harmonization and may decrease welfare. Harmonization upward has more beneficial long-run effects than harmonization downward, and also provides higher expected instantaneous benefits if the current stock is uncertain. In the short run there is a conflict between environmental protection and reduction of unemployment, but in the long run the two goals are consistent.
Keywords: Q20; F10; H23; 330; International trade and the environment; environmental policy reform; international harmonization of environmental policies; environmental dynamics and trade; Offene Volkswirtschaft; Internationale Umweltpolitik; Ökosteuer; Internationale Wirtschaft; Theorie